2015
DOI: 10.7603/s40681-015-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

An acute bleeding metastatic spinal tumor from HCC causes an acute onset of cauda equina syndrome

Abstract: Hepatocellular carcinoma (HCC) is an aggressive tumor that frequently occurs in the setting of chronic liver disease and cirrhosis. Herein, we describe a case where a patient presented with acute onset cauda equina syndrome due to an intradural and extramedullary metastatic tumor bleeding from hepatocellular carcinoma (HCC). The patient had lower back pain that had radiated to the bilateral lower legs for 3 weeks. Then, the patient had experienced an acute onset of bilateral lower leg weakness as well as bladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The global incidence of HCC varies considerably, with particularly high rates in Southeast Asia and sub-Saharan Africa, and lower, but increasing rates, in North America and most of Europe 2 . In Taiwan, HCC is the second leading cause of cancer-related deaths 3 , 4 . Enormous studies have indicated that high percentage of HCC progress with chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…The global incidence of HCC varies considerably, with particularly high rates in Southeast Asia and sub-Saharan Africa, and lower, but increasing rates, in North America and most of Europe 2 . In Taiwan, HCC is the second leading cause of cancer-related deaths 3 , 4 . Enormous studies have indicated that high percentage of HCC progress with chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Liver cancer is mainly a male disease, with approximately three times higher incidence and mortality among men than women. Hepatocellular carcinoma is one of the top 10 causes of cancer death worldwide (Jemal et al, 2011) and is an aggressive tumor (Wu et al, 2015). In addition, ERa was frequently found dysregulated in liver cancer and overexpression of b-catenin was observed in the nuclei of HCC patients (Lai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite improvements in surgical and medical treatments, recurrence and metastasis contributes to poor prognosis in HCC patients . Extrahepatic metastasis reportedly happens in 13.5–36.7% of cases, and HCC are known to metastasize on lungs, adrenal glands, bone marrow, and rarely on central nervous system . Therefore, understanding the molecular events and efficient targets that are involved in the survival and metastasis of HCC and to explore new therapeutically efficient factors targeting these mediators are imminent.…”
Section: Introductionmentioning
confidence: 99%